2017
DOI: 10.3348/kjr.2017.18.3.452
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Involvement of Recurrent Renal Cell Carcinoma: CT Findings and Clinicopathologic Features

Abstract: ObjectiveTo retrospectively evaluate the CT findings and clinicopathologic features in patients with gastrointestinal (GI) involvement of recurrent renal cell carcinoma (RCC).Materials and MethodsThe medical records were reviewed for 15 patients with 19 pathologically proven GI tract metastases of RCC. The CT findings were analyzed to determine the involved sites and type of involvement; lesion size, morphology, and contrast enhancement pattern; and occurrence of lymphadenopathy, ascites and other complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…In total, 50 KJR (9101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354565758), 492 ER, and 254 Radiology articles reported original research studies analyzing patient data. Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 50 KJR (9101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354565758), 492 ER, and 254 Radiology articles reported original research studies analyzing patient data. Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month. The point estimate value of this proportion was slightly larger in KJR than in ER and Radiology, although the difference was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…The differential diagnosis of a GI tumor includes GI stromal tumors, neuroendocrine tumors, lymphoma, and melanoma. 8 Classically, RCC and PAX8 staining would suggest renal origin, because these markers have been previously shown to stain 98% and 72% to 85% of clear cell renal cell carcinomas, respectively. 9 However, PAX8 can be positive in other tumor types such as carcinoma of Mullerian origin.…”
Section: Discussionmentioning
confidence: 99%
“…The actual prevalence of metastatic RCC to the small bowel is largely unknown. One cohort study of 3,637 patients with RCC identified 26 patients (0.71%) with pathologically proven RCC metastases to the GI tract [15]. However, this number only represents symptomatic cases that came to medical attention and had tissue confirmation and thus likely underestimates the true prevalence of disease.…”
Section: Discussionmentioning
confidence: 99%